ANALISIS DAN PERANCANGAN SISTEM INVENTARISASI ASET PADA PT. BANGUNINDO TEKNUSA JAYA - Agnes Meilosa Callysta; Magdalena Ariance Ineke Pakereng (Politeknik Bisnis Indonesia, 2022)
Asset inventory is an effort to collect data, record, report the results of asset data collection and then document it. PT. Bangunindo Teknusa Jaya is a technology company. Previously PT. Bangunindo Teknusa Jaya already has a website, but the website does not yet have a company asset inventory system. With the creation of an asset inventory system, it is hoped that this system can assist in recording asset loans and collecting company asset data. In making an asset inventory system, the method used is the Waterfall Method. The Waterfall Method has 5 steps: (1) Requirements, (2) Design, (3) Implementation, (4) Verification, and (5) Maintenance. Asset Inventory Information System PT. Bangunindo Teknusa Jaya is designed using Unified Modeling Language (UML) diagrams, namely Use Case Diagrams, Class Diagrams, and Activity Diagrams. The UML diagram of the asset inventory system uses StarUML tools, while the design of the asset inventory system uses MarvelApp. From the research that has been done, it produces a system that can help admins in saving time in data collection and transactions for borrowing company assets so that the admin's work becomes more effective and efficient.